The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1359105317727839
|View full text |Cite
|
Sign up to set email alerts
|

Unique relations between post-traumatic stress disorder symptoms and patient functioning in type 2 diabetes

Abstract: This study examined reported post-traumatic stress disorder symptoms in adults with poorly controlled type 2 diabetes who had no history of psychiatric diagnosis or treatment ( n = 184, M = 9.13%, standard deviation = 1.68). Participants reported moderate to severe intensity of post-traumatic stress disorder symptoms ( M = 19.17, SD = 17.58). Together, depressive and post-traumatic stress disorder symptoms accounted for 10-40 percent of the variance in type 2 diabetes outcomes; post-traumatic stress disorder s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
1
9
0
2
Order By: Relevance
“…Research into the relationship of PTSD and HCU is mixed, with some studies finding a decrease in clinic visits (likely because of avoidance behaviors) and others showing increased HCU. 10 , 25 Either scenario is going to increase direct costs, because deferring care, especially in the context of IBD, can lead to more severe disease and emergent treatments. Patients with CD did not differ from patients with UC for PCP visits, but patients with CD reported more GI clinic visits in the past year and more lifetime hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the relationship of PTSD and HCU is mixed, with some studies finding a decrease in clinic visits (likely because of avoidance behaviors) and others showing increased HCU. 10 , 25 Either scenario is going to increase direct costs, because deferring care, especially in the context of IBD, can lead to more severe disease and emergent treatments. Patients with CD did not differ from patients with UC for PCP visits, but patients with CD reported more GI clinic visits in the past year and more lifetime hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Patients with diabetic (64.7%) and hypertension (63.2%) have higher PTSS than patients with HIV-AIDS (27.5%). It was previously reported that patients with diabetic represent a group with considerable posttraumatic stress symptoms, which warrants increased attention in clinical care and research [34]. In the context of covid-19, diabetic and hypertension represent the two conditions reported to be mostly impacted by the reduction in healthcare system due to the pandemic, and the pandemic seems to have an indirect risk to these diseases through change in life style factors [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Each of the 9 included studies was a primary study that included data collection and analysis. The most common designs employed in the study were the cross-sectional [18,19], retrospective [20][21][22][23][24].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One of the risk factors not discussed in the previous subchapter is trauma. Eight articles [19,[21][22][23][24] included in this review examine the impact of traumatic experiences on the development of diabetes. Rau et al (2017) defined stress-induced hyperglycemia (SIH) as glucose levels above 250 mg/dL and found it to be associated with a 3.5-fold increase in the risk of mortality compared to patients showing diabetic normoglycemia [21].…”
Section: Stress Trauma and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation